Investigation of the outcome of patients with hip fractures using vitamin D3 - Ahmadreza Behrouzi; Hojat Hejazi; Alireza Kamali; Hoseinali Hadi (PAGEPress Publications, 2018)
Hip fracture is one of the important health problems of human societies. The aim of this study was to investigate the outcome of patients with this fracture using vitamin D3. This double-blind clinical trial was performed on 100 patients with hip fractures who referred to Valiasr Hospital. All specimens were evaluated for vitamin D3. Group A have had vitamin D3 in the normal range and received a dose of 50,000 vitamin D3 as blouse. Group B included individuals with hip fractures that did not have normal vitamin D3 levels. In this group, individuals received a dose of 50,000 units vitamin D3 in the form of muscular blouse, and then 50,000 units of vitamin D3 were given orally each week up to 12 weeks after surgery. After surgery, both groups were examined clinically and radiologically for ulcer and fracture healing. Moreover, mortality was checked 2 weeks after surgery and each month until healing. There was no significant difference in radiographic examination in the two groups in the term of adhesion and fracture union (P < 0.05). The formation of the union in the clinical examination 4 and 8 weeks after treatment in two groups showed significant difference. The formation of union in clinical presentation 4 weeks and 8 weeks after treatment in two groups showed significant difference (P = 0.005; P = 0.036). The results showed that a group with low vitamin D, but with supplementation, had more fracture union after 4 and 8 weeks after starting treatment. Vitamin D supplementation could improve patients' condition 4 and 8 weeks after treatment.